BANK WAKAF MIKRO SEBAGAI INSTRUMEN PENINGKATAN PRODUKTIVITAS USAHA MIKRO - Kusuma Wijaya, Siti Maulani; Ilmia, Anisa (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2021)
Micro Waqf Bank (BWM) is a Sharia Microfinance Institution established by the OJK with the hope of reducing poverty levels in Indonesia. Bank Wakaf Mikro is present in the pesantren environment to provide financial access for the middle to lower class society in order to get access to capital without collateral and low yields. This paper is expected to provide new knowledge and insights regarding one of the Islamic economic instruments in the micro sector, namely the Micro Waqf Bank model. This paper was prepared through the method of library research using secondary data. From observations from various literatures, Micro Waqf Bank with access to capital is one alternative for improving the standard of living of micro-entrepreneurs to develop their businesses. The ease of the process, accompanied by training and mentoring, is believed to be able to encourage the independence of the middle and lower classes in running micro-businesses and boost productivity in the real sector. With the role of pesantren which has great potential to develop the surrounding area.Keywords : Micro Waqf Bank (BWM), Micro business, Real sector, Sharia Microfinance Institutions